Phase 3 Trials of Thermosensitive Ciprofloxacin Gel for Middle Ear Effusion in Children with Tubes. (August 2016) - Park, Albert H.; White, David R.; Moss, Jonathan R.; Bear, Moraye; LeBel, Carl
Objective: To investigate the efficacy, safety, and microbiology of a thermosensitive otic suspension of ciprofloxacin (OTO-201) in children with bilateral middle ear effusion undergoing tympanostomy tube placement. Study Design: Two randomized, double-blind, sham-controlled phase 3 trials. Patients were randomized to intratympanic OTO-201 or sham. Setting: Children with bilateral middle ear effusion undergoing tympanostomy tube placement. Subjects/Methods: Studies evaluated 532 patients (6 months to 17 years old) in a combined analysis of efficacy (treatment failure: presence of otorrhea, otic or systemic antibiotic use, lost to follow-up, missed visits), safety (audiometry, otoscopy, tympanometry), and microbiology. Results: There was a lower cumulative proportion of treatment failures in patients receiving OTO-201 vs tympanostomy tubes alone (1) on days 4, 8, 15, and 29; (2) on day 15, primary end point (23.0% vs 45.1%; age-adjusted odds ratio, 0.341; P < .001; reduction in relative risk, 49%); and (3) on day 15, blinded-assessor otorrhea treatment failure (7.0% vs 19.4%; age-adjusted odds ratio, 0.303; P < .001; reduction in relative risk, 64%). Per-protocol and subgroup analyses (baseline demographics, pathogen type, culture status, effusion type, microbiologic response) supported these findings. There were no drug-related serious adverse events; the most frequent treatment-emergent adverse events in both groups were pyrexia, postoperative pain, nasopharyngitis, cough, and upper respiratory tract infection. OTO-201 administration had no evidence of increased tube occlusion and no negative effect on audiometry, tympanometry, or otoscopy. Conclusions: Combined analysis of 2 phase 3 trials demonstrated a lower cumulative proportion of treatment failures through day 15 compared with TT alone when OTO-201 was administered intratympanically for otitis media with bilateral middle ear effusion at time of tympanostomy tube placement.